The Growth Response of Jabon (Anthocephalus cadamba (Roxb.) Miq.) on The Application of Calcification in The Postmining Area RESPON PERTUMBUHAN TANAMAN JABON (Anthocephalus cadamba (Roxb.) Miq) TERHADAP PEMUPUKAN DAN PENGAPURAN DI AREAL BEKAS TAMBANG - Irdika Mansur; Arya Panji Wicaksono (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
The main problem of reclamation activities in the postmining land was marginal land that could not support the growth of plants, due to pH and the low level of nutrient. So that, the selection of local species which adaptable and the appropriate silviculture treatment was needed. Jabon (A. cadamba) is one of local tree species that had high prospect, because jabon classified into fast growing species, able to adapted various site conditions, and the silviculture treatment was relatively easy. Dolomit and gypsum were materials that contained of Ca (Calcium), which able being applied to increase the soil pH. This objectives research was to determine the effect of dolomit, crude gypsum and manure fertilizer on the growth of Jabon in postmining land at PT. Tunas Inti Abadi. The fertilizers treatment consisted of three treatments. There were 2 kg of manure fertilizer (N), 2 kg of manure fertilizer + 200 g of dolomit (KN), and 2 kg of manure fertilizer + gipsum 200 g (GN). The parameters that be measured were diameter, height, number of leaves, crown diameter and percentage of living. The combination of dolomit and manure fertilizear had significant effect on the 95% confidence interval the diameter of Jabon.Keywords: calcification, fertilizer, jabon, reclamation